Misreading the Court Decision: Reflecting on Constitutional Interpretation In Nusantara Capital Law Formation - Simanungkalit, Dedy; Vanny Vanny (Magister Hukum Universitas Semarang, 2025)
This study examines the use of Constitutional Court decisions in the academic manuscript of the Draft Law on the National Capital (RUU IKN) and evaluates its consistency with the 1945 Constitution, while drawing comparisons with governance models of other national capitals. The establishment of Ibu Kota Nusantara raises constitutional concerns because its governance design as an Authority excludes direct elections for regional leaders and the existence of a Regional House of Representatives. This design risks subordinating constitutional norms to political will, thereby undermining democratic principles. Using a normative juridical approach combined with comparative legal analysis, the research finds that the academic manuscript employs Constitutional Court rulings selectively, weakening constitutional guarantees of local democracy. Although the Court has recognized special governance status for certain regions, such as Papua and DKI Jakarta, these precedents have never eliminated democratic institutions, since both regions still maintain electoral and representative mechanisms. A comparison with Putrajaya, Malaysia, shows that centralistic governance may offer administrative efficiency but comes at the expense of political accountability and public participation. The study concludes that implementing the IKN Law without amendment will endanger constitutional legitimacy and set a harmful precedent for democratic governance. The novelty of this research lies in its critical perspective on how constitutional interpretation is instrumentalized in strategic policymaking, combining judicial analysis with comparative insights. Normatively, it recommends revising the IKN Law to align with constitutional principles of local democracy and strengthen safeguards for public participation and accountability.